2016
DOI: 10.1016/j.ijsu.2016.11.024
|View full text |Cite
|
Sign up to set email alerts
|

The role of the microbiome in kidney stone formation

Abstract: Nephrolithiasis is a complex disease of worldwide prevalence that is influenced by both genetic and environmental factors. About 75% of kidney stones are predominantly composed of calcium oxalate and urinary oxalate is considered a crucial risk factor. Microorganisms may have a role in the pathogenesis and prevention of kidney stones and the involvement of the intestinal microbiome in this renal disease has been a recent area of interest. Oxalobacter formigenes is a gram negative bacteria that degrades oxalate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 32 publications
1
52
1
4
Order By: Relevance
“…Urinary emergency and other chronic urinary tract symptoms have been associated with modification of bacterial components of urine (5,9,10). Patients who tend to have kidney stones seem to have different gut and urinary microbiota compared to that of healthy control patients (17). Difference in stone formation prevalence is also seen between vegetarians and meat eaters, which has been attributed to the difference in protein consumption but could result from different urinary microbiota (18).…”
Section: Human Urinary Microbiota and Clinical Microbiology Implicationsmentioning
confidence: 99%
“…Urinary emergency and other chronic urinary tract symptoms have been associated with modification of bacterial components of urine (5,9,10). Patients who tend to have kidney stones seem to have different gut and urinary microbiota compared to that of healthy control patients (17). Difference in stone formation prevalence is also seen between vegetarians and meat eaters, which has been attributed to the difference in protein consumption but could result from different urinary microbiota (18).…”
Section: Human Urinary Microbiota and Clinical Microbiology Implicationsmentioning
confidence: 99%
“…Approximately 75% of all kidney stones are composed primarily of calcium oxalate, with hyperoxaluria considered to be a primary risk factor for this type of stones (Liebman & Al‐Wahsh, ). Recent studies have shown that bacterial degradation of oxalate in the intestine decreases oxalate absorption, and a reduction in the urinary oxalate level decreases the incidence of calcium oxalate stone formation (Mehta et al ., ; Zhao et al ., ). In addition, several studies proposed that Lactobacillus and Bifidobacterium species possess oxalate degrading activity and documented a significant reduction in urinary oxalate levels associated with probiotic administration in both animals and humans (Campieri et al ., ; Weese et al ., ; Lieske et al ., ; Murphy et al ., ; Okombo & Liebma, ).…”
Section: Introductionmentioning
confidence: 99%
“…hypertension can cause an increase in calcium, a secretion gout increased uric acid secretion low fluid and fluid intake just makes a higher concentration of the urine and makes the urine more likely to crystallize acidic urine can make acidic substances crystallize and UTI with infection from urease positive bugs like Proteus [14] and Klebsiella can lead to pneumonia formation which can lead to the formation of history white stones.…”
Section: Discussionmentioning
confidence: 99%